1996
DOI: 10.1002/anie.199603311
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tailor‐Made Glycoconjugates Showing AT III‐Mediated Inhibition of Blood Coagulation Factors Xa and Thrombin

Abstract: The sulfated glycosaminoglycan heparin binds with high affinity to the plasma protein antithrombin 111 (ATIII), thereby accelerating its inhibitory activity towards factor Xa and thrombin, two serine proteases involved in blood coagulation.".The AT 111-binding region in heparin consists of a unique pentasaccharide (PS) domain,[3. 41 the synthetic counterpart of which was found to accelerate the ATIII-mediated inhibition of factor Xa but not that of t h r~m b i n . [~,~] In the course of studies on the prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The solution was gently stirred and degassed for another 30 min. Then PS 5, 6, or 7 [23] (23 mg, 2.5 equiv) was added as a solid, followed by the addition of NH 2 OH (50 mL, 0.05 m). The reaction mixture was stirred under a nitrogen atmosphere at ambient temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution was gently stirred and degassed for another 30 min. Then PS 5, 6, or 7 [23] (23 mg, 2.5 equiv) was added as a solid, followed by the addition of NH 2 OH (50 mL, 0.05 m). The reaction mixture was stirred under a nitrogen atmosphere at ambient temperature.…”
Section: Methodsmentioning
confidence: 99%
“…To assess whether the half-life of the insulin conjugates can be tuned by altering the affinity for ATIII, three different carrier PSs (PS 1 , PS 2 , or PS 3 ) [22,23] were introduced into recombinant human (recH) insulin with a pharmacologically inactive ethylene glycol spacer using thiol-maleimide coupling [24] chemistry (see Scheme 1 and Supporting Information). Thus, the two complementary di-N-Boc-protected [5b, 25] recH insulins 1 or 3 were treated with the succinic ester derivative of g-maleimidobutyric acid (GMB) to give, after acidic removal of the NBoc groups and purification by preparative HPLC, the B1-GMB and B29-GMB insulins 2 and 4, respectively.…”
mentioning
confidence: 99%
“…This finding informed the design of tailor‐made glycoconjgugates such as 8 and 9 (Figure ) with the full anticoagulant properties of heparin, consisting of synthetic ABD and TBD domains linked through a molecular spacer. Initially, a nonglycosaminoglycan ABD pentasaccharide (i.e., idraparinux) was connected via a molecular spacer to a persulfated maltotrioside as the TBD . This study revealed that the anticoagulant activity was dependent on all three domains of the conjugate.…”
Section: Heparin Mimeticsmentioning
confidence: 99%
“…Synthetic tailor‐made glycoconjugates consisting of ABD and TBD through flexible ( 8 ) and rigid ( 9 ) molecular spacers…”
Section: Heparin Mimeticsmentioning
confidence: 99%
“…Sulfated pentasaccharide connected to different spacers (charged, neutral, linear, flexible or rigid) were prepared in order to obtain heparin-like oligosaccharides with full anticoagulant properties [94,95]. Hindsgaul and co-workers [98] have shown that evaluation of carbohybrid libraries composed of D-galactopyranose that carry a diverse range of small non-carbohydrate aglycon structures led to the identification of M inhibitors of a galactose binding plant lectin.…”
Section: Glycosides and Spaced Sugarsmentioning
confidence: 99%